Quorum Sensing Inhibitor Activities of Celecoxib Derivatives in Pseudomonas aeruginosa - TINAZ, GÜLGÜN; ŞENKARDEŞ, SEVİL; KÜÇÜKGÜZEL, ŞÜKRİYE GÜNİZ (BENTHAM SCIENCE PUBL LTD, 2017)
Background: A series of novel N-(substituted aryl/alkylcarbamothioyl)-4-[5-(4-methylphenyl)3-( trifluoromethyl)-1H-pyrazol-1-yl] benzene sulfonamides [SGK 318, 319, 320, 324, 327] and N-(3-substitutedaryl/ alkyl-4-oxo-1,3-thiazolidin-2-ylidene)-4-[5-(4-methylphenyl)-3-(trifluoromethyl)-1H-pyrazol-1-yl] benzenesulfonamides[SGK 328, 329, 330, 334, 337] were synthesized and tested for their quorum sensing inhibitor (QSI) capacity using quorum sensing inhibitor selector 1 (QSIS1) bioassay. Findings: QSIS assay revealed that SGK 324, SGK 327 and SGK 330 have the potentials to interfere with QS system in QS inhibitor selector1 (QSIS1) reporter strain. Moreover, these compounds were found to significantly affect QS regulated elastase and biofilm productions in Pseudomonas aeruginosa PA01 strain without affecting its growth. Molecular modeling experiments suggested that SGK 330 fits within the binding site of LasR protein of P. aeruginosa. SGK 324 and 327 also bind LasR provided that they adopt a s-trans/s-cis conformation with respect to the thiourea function. Results and Conclusion: Results of this study indicated that these compounds could be developed as new QS inhibitors without killing the bacteria but as antivirulence compounds to restrict virulence of clinically important human pathogens.
Keywords: Celecoxib; sulfonylthioureido; 4-thiazolidinone; LasR protein; Pseudomonas aeruginosa; quorum sensing; BACTERIAL COMMUNICATION; INFECTIOUS-DISEASES; BIOFILM; DRUGS; IDENTIFICATION; VIRULENCE; MUTANT